Low temperature specifications for asphalt binders: tests and simulation - Babadopulos, Lucas F. A. Lima; Le Guern, Malo; Chailleux, Emmanuel; Dreessen, Sylvia (Transportes, 2011)
Low temperature specifications for asphalt binders: tests and simulation